2010
DOI: 10.1038/onc.2010.238
|View full text |Cite
|
Sign up to set email alerts
|

Acquired radioresistance of human tumor cells by DNA-PK/AKT/GSK3β-mediated cyclin D1 overexpression

Abstract: Recurrence is frequently associated with the acquisition of radioresistance by tumors and resulting failures in radiotherapy. We report, in this study, that long-term fractionated radiation (FR) exposures conferred radioresistance to the human tumor cells, HepG2 and HeLa with cyclin D1 overexpression. A positive feedback loop was responsible for the cyclin D1 overexpression in which constitutively active AKT was involved. AKT is known to inactivate glycogen synthase kinase-3b (GSK3b), which is essential for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
150
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(157 citation statements)
references
References 45 publications
7
150
0
Order By: Relevance
“…Previous studies revealed that elevated levels of cyclin D1 confer radiation resistance of cancer cells (29,30) and high levels of cyclin D1 correlate with unfavorable response to radiotherapy (31,32). Conversely, suppression of cyclin D1 sensitizes cancer cells to DNA damage (29,33).…”
Section: P16ink4a Inhibits Recruitment Of Rad51 To the Sites Of Dna Dmentioning
confidence: 99%
“…Previous studies revealed that elevated levels of cyclin D1 confer radiation resistance of cancer cells (29,30) and high levels of cyclin D1 correlate with unfavorable response to radiotherapy (31,32). Conversely, suppression of cyclin D1 sensitizes cancer cells to DNA damage (29,33).…”
Section: P16ink4a Inhibits Recruitment Of Rad51 To the Sites Of Dna Dmentioning
confidence: 99%
“…Radiosensitivity can be influenced by both intrinsic and extrinsic factors such as hypoxia (Rockwell et al 2009; 532654J HCXXX10.1369/0022155414532654Shen et alCorrelation of SOX2 and OCT4 with Radiation Resistance research-article2014 Dewhirst et al 2008), the cell cycle (Shimura et al 2010;He et al 2011), DNA damage and repair (Bolderson et al 2009;Beskow et al 2009), apoptosis (Lehmann et al 2007;Suzuki et al 2007), growth factors and oncogenes (Mukherjee et al 2009;Bergkvist et al 2011), cancer stem cells (CSCs) and the epigenetic modification of genes (Baumann et al 2008;Kawano et al 2010). CSCs, which have been recognized as a source of local or distant cancer relapse, have the potential to dramatically affect clinical outcomes (Brunner et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The radioresistance of human tumor cells can be achieved via aberrantly activated DDR signaling The cells were treated with 2.5 and 5 Gy radiation, and the surviving fraction was calculated based on the number of colonies in the soft agar clonogenic assay. (Shimura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%